Study on Pseudo-Biological Highly Performance Capillary-welded Hybrid Diameters Silver Nanowires Transparent Electrodes for Optoelectronic Devices - Yang, Lianqiao; Wang, Pengchang; Li, Yiru; Zhang, Jianhua (New Approaches in Engineering Research Vol. 5, 2021)
Graphene/silver nanowire composite films have great potential as transparent conductive electrodes in the field of optoelectronic devices. So far, antioxidant and reducing the junction resistance are two major parameters in the silver nanowire electrode studies. In this paper, a pseudo-biological inspired structure for transparent electrodes was proposed by combining hybrid diameters silver nanowire network with the chemical vapor deposition-grown (CVD-grown) graphene as a passivation layer. An environmentally friendly liquid, deionized water, was selected for the generation of capillary forces at the liquid bridge, thereby improving the wire junction problem. Compared with the silver nanowire films, the value of the figure of merit (FoM) of the graphene/silver nanowire composite film increased by 69.6% with a sheet resistance of 26.4 ?/sq, and a transmittance was 91.4% at 550nm. Also, graphene was chosen as an encapsulation layer to protecting silver nanowires from oxidation while improving electrical properties, which makes the composite films promising as electrodes for underwater optoelectronic devices or a possible development in high humidity environments. Furthermore, the capillary-welded silver nanowire/graphene composite film was used as the transparent anode to prepare organic light-emitting diode (OLED) devices. The devices emitted green electroluminescence at 516 nm, and the turn-on voltage was about 3.8 V. The maximum brightness was 50810 cd/cm2, which is higher than the indium tin oxide-based (ITO-based) devices with the same configuration. Therefore, it means that this novel silver nanowires/graphene electrode has great potential in optoelectronic device applications.